Sol-gel synthesis of vanadium phosphorous oxides for the partial oxidation of n-butane to maleic anhydride - Salazar, Juan Manuel (Kansas State University, 2007)
Vanadium phosphorous oxide (VPO) is traditionally manufactured from solid vanadium oxides by synthesizing VOHPO[4subscript][dot in middle of line]0.5H[2subscript]O (the precursor) followed by in-situ activation to produce (VO)[2subscript]P[2subscript]O[subscript]7 (the active phase). These catalysts considerably improve their performance when prepared as nanostructured materials and this study discusses an alternative synthesis method based on sol-gel techniques capable of producing nanostructured VPO. Vanadium(V) triisopropoxide oxide was reacted with ortho-phosphoric acid in tetrahydrofuran (THF). This procedure yielded a gel of VOPO[4subscript] with interlayer entrapped molecules. The gels were dried at high pressure in an autoclave with controlled excess and composition of THF-2-propanol mixtures. The surface area of the obtained materials was between 50 and 120 m[2superscript]/g. Alcohol produced by the alkoxide hydrolysis and incorporated along with the excess solvent reduced the vanadium during the drying step. Therefore, after the autoclave drying, the solid VOPO[4subscript] was converted to the precursor; and, non-agglomerated platelets were observed. Use of additional 2-propanol increased the amount of precursor in the powder but reduced its surface area and increased its crystallite size. In general, sol-gel prepared catalysts were significantly more selective than the traditionally prepared materials, and it is suggested that the small crystallite size obtained in the precursor influenced the crystallite size of the active phase increasing their selectivity towards maleic anhydride. The evaluation of these materials as catalysts for the partial oxidation of n-butane at 673 K under mixtures of 1.5% n-butane in air yielded selectivity of 40% at 50% conversion compared to 25% selectivity at similar level of conversion produced by the traditionally prepared catalysts. Variations in the catalytic performance are attributed to observed polymorphism in the activated materials, which is evidenced by remarkable differences in the intrinsic activity. All precursors and catalysts were characterized by IR, XRD, SEM and BET, and the products of the catalytic tests were analyzed by GC.
Keywords: Butane oxidation (partial); Maleic anhydride; Sol-gel process; Supercritical drying; Vanadium alkoxides; Vanadium phosphorous oxide catalysts; Chemistry, General (0485); Chemistry, Inorganic (0488); Engineering, Chemical (0542)